Carbon farming: A pathway to mitigate climate change for sustainable agriculture - Gokul, S; Manivannan, V; Thirukumaran, K; Boominathan, P; Nagarajan, K; Asritha, M (Plant Science Today, 2025)
In the twenty-first century, climate change results in a combination of natural and human impacts, including extreme weather and variability. Carbon farming has the opportunity to significantly reduce global warming while increasing resilience. Carbon farming is a holistic agricultural practice that seeks to minimize climate change and enhance ecologically sound sustainable farming. Enhancing soil and vegetation’s potential to capture atmospheric carbon dioxide (CO2) may assist in mitigating greenhouse gas emissions while also enhancing soil health and agricultural productivity. This review explores the key carbon farming practices such as conservation agriculture (CA), agroforestry, cover cropping, intercropping, tillage practices and mulching and their role in promoting soil organic carbon and reducing greenhouse gas (GHG) emissions. Global programs such as the Agricultural Carbon Project in Australia and Kenya, the Chicago Climate Exchange and the 4 of 1000 Initiative, indicate that carbon farming might boost food security while simultaneously addressing climate change. High-impact regions can enjoy economic gains amounting to as much as 63 billion from things like crop rotation and organic farming under the umbrella of emissions trading initiatives that encourage environmentally sound agricultural techniques. However, drawbacks include a lack of financial assistance, ineffective policies and restricted supply of water. Carbon farming may be efficiently promoted with strong government assistance, financial incentives and improved stakeholder awareness. Through increased adoption of carbon farming practices, agriculture becomes more resilient, sustainable and aligned with sustainable development goals (SDG).